ACTIVITY-BASED COSTING AS INFORMATION BASIS FOR EFFICIENT STRATEGIC MANAGEMENT PROCESS - Kaličanin, Đorđe; Knežević, Vladan (Economic Annals, 2013)
Activity-based costing (ABC) provides an information basis for monitoring and controlling one of two possible sources of competitive advantage, low-cost production and low-cost distribution. On the basis of cost information about particular processes and activities, management may determine their contribution to the success of a company, and may decide to transfer certain processes and activities to another company. Accuracy of cost information is conditioned by finding an adequate relation between overhead costs and cost objects, identifying and tracing cost drivers and output measures of activities, and by monitoring cost behaviour of different levels of a product. Basic characteristics of the ABC approach, such as more accurate cost price accounting of objects, focusing on process and activity output (rather than only on resource consumption) and on understanding and interpretation of cost structure (rather than on cost measurement), enable managers to estimate and control future costs more reliably. Thus the ABC methodology provides a foundation for cost tracing, analysis, and management, which entails making quality and accurate operative and strategic decisions as a basis for the long-term orientation of a company. ABC is also complementary to the widely accepted technique of strategic planning and strategy implementation known as Balanced Scorecard (BSC).